ANALISIS YURIDIS PERTANGGUNGJAWABAN TINDAK PIDANA PEMBANTUAN/ MEDEPLICHTIGEDALAM KASUS KERUSUHAN DEMONSTRASI - Vannesah Nara Tasya Halim; Ferawati Ferawati; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The decision of the Panel of Judges at the Central Jakarta District Court in the criminalcase Number: 844/Pid.B/2019/PN.Jkt.Pst, is one of the cases of national concern. The decisionrelates to the Crime of Assistance/Medeplichtige which raises questions regarding what is thejudge's benchmark in deciding the case so that the defendants are interpreted as actorsparticipating in assisting anarchist crimes and what actions can be categorized as assistancein a crime, because in that case it was found that the co-perpetrator of giving drinking waterand water for washing his face to the participants in the riot action during the demonstrationwas sentenced to a criminal sentence even though he had no malicious intent to commit acrime. The purpose of this research is to find out the liability for the criminal assistance/medeplichtige and to find out the suitability between the arrangements regarding the crime ofassisting/ medeplichtige and decision No.844/Pid.B/2019/PN.Jak.Pst related to thedemonstration riot case.The results of this study there are two main points. First, that accountability related tocriminal acts of assistance/medeplichtige in Indonesia is regulated in Article 57 of the CriminalCode where in the decision related to the demonstration riot case there are reasons that cannegate accountability in a person. Second, after outlining and analyzing the related decisions,it was found that there was a judge's mistake in interpreting the suitability between the actionscommitted by the Defendants and the arrangement for co-operation crimes because there wasno causality between the act and the circumstances after the act was committed and the judge'sjudgments or judgments in this case were not objective, because it is not based on the factsrevealed in court.Keywords: Medeplichtige-Demonstration-Criminal Liability